Effects of caffeine on countermovement-jump performance variables in elite male volleyball players - Zbinden-Foncea, H.; Rada, I.; Gomez, J.; Kokaly, M.; Stellingwerff, T.; Deldicque, L.; Peñailillo, L. (International Journal of Sports Physiology and Performance, 2018)
Purpose: To examine the effects of a moderate dose of caffeine in elite male volleyball players on countermovement-jump (CMJ) performance, as well as temporal concentric- and eccentric-phase effects. Methods: Ten elite male volleyball players took part in 2 experimental days via a randomized crossover trial 1 wk apart in which they ingested either 5 mg/kg of caffeine or a placebo in double-blind fashion. Heart rate and blood pressure were measured at rest and 60 min postingestion. Afterward, subjects also performed 3 CMJ trials 60 min postingestion, of which the average was used for further analysis. They filled out a questionnaire on possible side effects 24 h posttrial. Results: Caffeine intake, compared with placebo, increased CMJ peak concentric force (6.5%±6.4%; P=.01), peak power (16.2%±8.3%; P<.01), flight time (5.3%±3.4%; P<.01), velocity at peak power (10.6%±8.0%; P<.01), peak displacement (10.8%±6.5%; P<.01), peak velocity (12.6%±7.4%; P<.01), peak acceleration (13.5%±8.5%; P<.01), and the force developed at peak power (6.0%±4.0%; P<.01) and reduced the time between peak power and peak force (16.7%±21.6%, P=.04). Caffeine increased diastolic blood pressure by 13.0%±8.9% (P<.05), whereas no adverse side effects were found. Conclusions: The ingestion of 5 mg/kg of anhydrous caffeine improves overall CMJ performance without inducing side effects.